Destiny, the inward quest, temporality and life - Tymieniecka, A-T.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
There is no greater gift to man than to understand nothing of his fate, declares poet-philosopher Paul Valery. And yet the searching human being seeks ceaselessly to disentangle the networks of experiences, desires, inward promptings, personal ambitions, and elevated strivings which directed his/hers life-course within changing circumstances in order to discover his sense of life. Literature seeks in numerous channels of insight the dominant threads of the sense of life, the inward quest, the frames of experience in reaching the inward sources of what we call destiny inspired by experience and temporality which carry it on. This unusual collection reveals the deeper generative elements which form sense of life stretching between destiny and doom. They escape attention in their metamorphic transformations of the inexorable, irreversibility of time which undergoes different interpretations in the phases examining our life. Our key to life has to be ever discovered a new.
INAUGURAL ADDRESS: Anna-Teresa Tymieniecka; SECTION I: THE SENSE OF LIFE PRESENT ETERNITY: QUESTS OF TEMPORALITY IN THE LITERARY PRODUCTION OF THE <<EXTREME CONTEMPORAIN>> IN FRANCE (THE WRITINGS OF DOMINIQUE FOURCADE AND EMMANUEL HOCQUARD) Silvia Riva; A SENSE OF LIFE IN LANGUAGE LOVE AND LITERATURE Lawrence Kimmel; THE GARDEN THEN AND NOW; SENSE OF LIFE CONTEMPORARY AND IN GENESIS Bernadette Prochaska; THE STREAM OF CONSCIOUSNESS: LITERARY PSYCHOLOGY AS THE FIRST UNIQUELY AMERICAN EXPRESSION OF PHENOMENOLOGY IN WILLIAM JAMES AND HIS SWEDENBORGIAN AND TRANSCENDENTALIST MILIEU Eugene Taylor; SECTION II: THE INWARD QUEST THE EVOLUTION OF JUSTICE IN THE ORESTEIA Heidi Silcox; A DOUBLE PHENOMENOLOGICAL SENSE OF THE HYBRID OF FATE AND DESTINY IN COMMUNITY IN ACHEBE?S ARROW AND HEAD?S TREASURES Imafedia Okhamafe; WHAT MASIE KNEW IN WHAT MASIE KNEW Victor Gerald Rivas; STYLE MATTERS: THE LIFE-WORLDS OF ANCIENT LITERATURE Damian Stocking; JAMES JOYCE?S IVY DAY IN THE COMMITTEE ROOM AND THE FIVE CODES OF FICTION Raymond Wilson; SECTION III: HISTORICITY AND LIFE TEMPORALITY IN FITZGERALD'S BABYLON REVISITED Bernadette Prochaska; ON THE METAPHYSICAL BRUTISHNESS OF LIFE IN THE LIGHT OF ZOLA'S THE HUMAN BEAST Victor G. Rivas; ?MAIS PERSONNE NE PARAISSAIT COMPRENDRE? (?BUT NO ONE SEEMED TO UNDERSTAND?): ATHEISM, NIHILISM, AND HERMENEUTICS IN ALBERT CAMUS? L?ETRANGER / THE STRANGER George Heffernan; HISTORICAL DISTORTIONS AND LITERARY DISCLOSURES IN D.M. THOMAS?S THE WHITE HOTEL Lewis Livesay; MORAL SHAPES OF TIME IN HENRY JAMES Meili Steele; SECTION IV: THE LIMITS OF ORDINARY EXPERIENCE ?THE LIMITS OF ORDINARY EXPERIENCE?: A PHENOMENOLOGICAL READING OF RAPPACCINI?S DAUGHTER R. Kenneth Kirby; GOING BEYOND THE SELF AS THE KNOWLEDGE OF ONESELF AND THE SENSE OF THE UNIVERSE Bronislaw Bombala; THE KINDNESS OF STRANGERS: EPIPHANY AND SOCIAL COMMUNION IN PAUL THEROUX?S TRAVEL WRITING Bruce Ross; EMERSON AFFINITIES: READING RICHARD FORD THROUGH STANLEY CAVELL Lawrence F. Rhu; FAULKNER?S THE SOUND AND THE FURY AS ANTI-ENTROPIC NOVEL Jerre Collins; SECTION V: DESTINY, EXPERIENCE AND TIME W.B. YEATS, UNITY OF CULTURE, AND THE SPIRITUAL TELOS OF IRELAND R. Kenneth Kirby; DOOM, DESTINY, AND GRACE: THE PRODIGAL SON IN MARILYNNE ROBINSON?S HOME Rebecca M. Painter; MAN?S DESTINY IN TISCHNER?S PHILOSOPHY OF DRAMA Leszek Pyra; THE SOURCE FORM, AND GOAL OF ART IN ANTON CHEKHOV?S THE SEA GULL Raymond J. Wilson, III; SECTION VI: THE ARTISTIC QUEST VERSUS THE DISCERNMENT OF TRUTH A SHORT STUDY OF THE JAPANESE RENGA: THE TRANS-SUBJECTIVE CREATION OF POETIC ATMOSPHERE: Tadashi Ogawa; ALTERED STATES: THE ARTISTIC QUEST IN THE STONE FLOWER AND LA SYLPHIDE Bruce Ross; TOO MUCH HAPPINESS, TOO MUCH SUFFERING? NEVER ENOUGH REALITY TRANSFORMED BY NARRATIVE Rebecca Painter; THE PHENOMENOLOGY OF MERLEAU-PONTY AND LITERARY ARTS Piotr Mroz; REVISITING STEINBECK?S LITTORAL PHENOMENOLOGY: HUSSERLIAN ELEMENTS IN THE LOG FROM THE ?SEA OF CORTEZ? Gretchen Gusich; THE ROLE OF ART IN CAMUS AND SARTRE Joanna Handerek; STAGING HEIDEGGER: CORPOREAL PHILOSOPHY, COGNITIVE SCIENCE, AND THE THEATER Thomas Blake; INDEX OF NAMES; PROGRAMS FROM THE 2009 AND 2010 PHENOMENOLOGY AND LITERATURE CONFERENCES
Keywords: Teleology; Fate and fatalism; Electronic books